Dietary intake is compromised among elderly living in agricultural settlements - Zainudin, Norain; Hamirudin, Aliza Haslinda; Sidek, Suriati; A. Rahman, Nor Azlina (Emerald Group Publishing Ltd., 2019)
Purpose – This study aims to investigate dietary intake among elderly living in agricultural settlements in comparison with a recent nutritional recommendation. Design/methodology/approach – This cross-sectional study was carried out among elderly living in five agricultural settlements in Kuantan, Pahang, Malaysia. Participants were interviewed on sociodemographic information such as age, gender, marital status, smoking status, household income, education level and living status. Data on individual dietary intake were obtained through diet history method. Dietary intake data were analyzed using Nutritionist Pro software and compared to the recommended nutrient intakes (RNI) for Malaysia version 2017. Statistical analyses were performed using SPSS software version 21. Findings – A total of 413 participants (male 32.4 per cent and female 67.6 per cent) with the mean age of 69.4 ± 7.9 years participated in this study. Dietary intake results demonstrated that participants did not meet the Malaysian RNI for energy and most nutrients (p<0.05). This study also found that energy, carbohydrate, protein, fat, folate and iron intake were significantly higher in male than female (p<0.05). Meanwhile, calcium and vitamin A intake were significantly higher in female than male (p<0.05). Research limitations/implications – Integrated nutrition education and health promotion programme with a multidisciplinary approach are essential to be designed and executed to improve dietary intake of the elderly, which can further lead to appropriate dietary practices and knowledge improvement related to healthy food choices. Factors associated with inadequate dietary intake and awareness on the importance of adequate nutrients intake among the elderly warrant further investigation. Originality/value – This research is at the forefront, which indicated that the dietary intake of elderly individuals living in the agricultural settlement was inadequate in comparison to the latest recommendation. Strategies to improve their intakes need to be developed and implemented accordingly to improve nutritional status and prevent adverse effects to health.